MANAJEMEN DAN KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA - Agung Kurniawan S. Djibran (CV. ADIBA AISHA AMIRA, 2025)
Education requires input from various parties in the formulation of its policies. Given that the moral crisis is escalating, strict educational management is needed. Education is a process of instilling and developing values and norms that are implicit in every subject, including Islamic education and its teachers. Therefore, it is not only Islamic education teachers who have the responsibility to educate students' morals and character, but this also applies to all educators. Efforts to improve the quality of Islamic education have been widely implemented. The aim is to convey the meaning of education that serves to build the character and morals of a dignified nation in order to educate the nation, develop the potential of Indonesians who are faithful and devoted to God Almighty, have noble morals, are healthy, knowledgeable, skilled, creative, and independent. The shortcomings and strengths of each school will have an impact and require different approaches. Appropriate policies and management will yield positive outcomes aligned with the institution's objectives. Conversely, if management and policies are not tailored to the institution's needs, failure is inevitable. Do not merely focus on the policies and management of other institutions that appear effective and successful. Every institution has different needs and objectives, so policies and management in each school will also differ and should be tailored to their respective needs.